2007
DOI: 10.1038/emm.2007.54
|View full text |Cite
|
Sign up to set email alerts
|

Akt is involved in the inhibition of cell proliferation by EGF

Abstract: Axin is a negative regulator of the Wnt/β-catenin pathway and is involved in the regulation of axis formation and proliferation. Involvement of Axin in the regulation of other signaling pathways is poorly understood. In this study, we investigated the involvement of Akt in growth regulation by Axin in L929 fibroblasts stimulated by EGF. Akt activity was increased by EGF treatment and Ras activation, respectively. Both the EGFand Ras-induced Akt activations were abolished by Axin induction, as revealed by both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The P13K and ERK are too triggered by Wnt3a, and that is allied with cellular propagation [54, 55]. Auxiliary numerous observations have been confirmed control of the RAF-1-MEK-ERK signaling cascade by the Wnt/β-catenin signaling [5658]. Additionally, GSK3β, chief player of Wnt/β-catenin pathway, is controlled by RAS-MAPK and PI3 K-Akt signaling cascades, and the cross-talk between GSK3β and RAS-MAPK or PI3K/AKT/mTOR signaling pathways is implicated in the pathogenesis of HCC and pancreatic cancer [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…The P13K and ERK are too triggered by Wnt3a, and that is allied with cellular propagation [54, 55]. Auxiliary numerous observations have been confirmed control of the RAF-1-MEK-ERK signaling cascade by the Wnt/β-catenin signaling [5658]. Additionally, GSK3β, chief player of Wnt/β-catenin pathway, is controlled by RAS-MAPK and PI3 K-Akt signaling cascades, and the cross-talk between GSK3β and RAS-MAPK or PI3K/AKT/mTOR signaling pathways is implicated in the pathogenesis of HCC and pancreatic cancer [59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Recent published data show that the connecting link between the two pathways is Axin, a negative regulator of the canonic Wnt pathway/␤-catenin signaling pathway, 22 which is responsible for downregulation of ␤-catenin signaling, acting in a negative feedback loop via Akt. 23,24 Our data showed that incubation of cells in EGF resulted in a decrease in ␤-catenin and GSK-3␤ transcription and translation comparable to IGF-1 data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of the MEK/ERK 1/2 cascade regulated fibroblast proliferation induced by insulin growth factor-I (54) and by muscarinic receptor stimulation (47). Other authors showed the activation of both the MEK/ ERK pathway and the PI3K/Akt pathway in fibroblast proliferation stimulated with ionizing radiation (37) or EGF (31). Moreover, the PI3K-Akt pathway mediates growth and proliferation induced by Wnt3a protein in NIH3T3 (39) and in renal fibroblasts (79).…”
Section: Discussionmentioning
confidence: 99%